FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK IBU DALAM MENCEGAH PAPARAN ASAP ROKOK PADA BALITA PEROKOK PASIF - Tiara Budi Indrajati; VG Tinuk Istiarti; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Cigarettes are cylinders of paper containing tobacco leaves with one of  the side of paper burned so that the smoke can be inhaled through the mouth from the other side (active smokers) and can be inhaled by people around (passive smokers). The remaining smoke exhaled by active smokers is dangerous because it can survive in the air for more than two and a half hours and unconsciously can be inhaled by a toddler unnoticed by their parents. The purpose of this study is to analyze factors related to mother’s practices in preventing exposure to secondhand smoke in toddlers.The type of this research is descriptive analytic with quantitative approach. The research design was cross sectional. Samples taken as many as 95 respondents. (mothers who have children under five age in Pedurungan District, Semarang City). The instrument used in the form of questionnaires with interviews. Data analysis was univariate and bivariate with chi-square test.The results showed that the age of the respondents was dominated by respondents with 30 years old and the last education completed high school or vocational school. The average respondent did not work equal to 54,7%. The results showed that education (p = 0,131), and occupation (p = 0,915) were not related to mother practice in preventing exposure of cigarette smoke. While knowledge (p = 0,004) and attitude (p = 0,013), relate to mother practice in preventing exposure of cigarette smoke.The conclusion of this research is found that factors related to mother practice in preventing exposure of secondhand smoke to passive smoker is knowledge and attitude. The suggestion given by the researcher is needed to giving the material about the exposure of cigarette smoke for the mother of toddler and especially for the person who smoke by giving print out material for easy understood.